2021
DOI: 10.1002/ps.6261
|View full text |Cite
|
Sign up to set email alerts
|

The role of Desmodium intortum, Brachiaria sp. and Phaseolus vulgaris in the management of fall armyworm Spodoptera frugiperda (J. E. Smith) in maize cropping systems in Africa

Abstract: BACKGROUND The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) is a serious pest of maize. Farming systems such as push‐pull or maize‐legume intercropping have been reported to reduce FAW infestations significantly. However, the exact mechanisms involved in FAW management have not been practically elucidated. We therefore assessed larval host preference, feeding and survival rate when exposed to four host plants commonly used in push‐pull and legume intercropping. We also compared adult moths' oviposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For example, several studies have reported that maize intercropped with legumes had the greatest diversity and abundance of natural enemies, including a number of parasitoids known to attack S. frugiperda (J. E. Smith), a Lepidopteran pest attributed to up to 60% yield damage in some maize-producing regions globally ( Jiménez-Martínez & Gómez-Martinez, 2013 ; Goergen et al, 2016 ). Similar results were also reported by Scheidegger et al (2021) . To address the likelihood that phytophagous insects would spread into new areas and destroy maize crops in intercropping systems, a comprehensive study of the effect of maize-legume intercrops on the diversity and abundance of entomofauna is needed to create techniques that could be used to reduce the potential for pest infestations.…”
Section: Survey Methodologysupporting
confidence: 92%
“…For example, several studies have reported that maize intercropped with legumes had the greatest diversity and abundance of natural enemies, including a number of parasitoids known to attack S. frugiperda (J. E. Smith), a Lepidopteran pest attributed to up to 60% yield damage in some maize-producing regions globally ( Jiménez-Martínez & Gómez-Martinez, 2013 ; Goergen et al, 2016 ). Similar results were also reported by Scheidegger et al (2021) . To address the likelihood that phytophagous insects would spread into new areas and destroy maize crops in intercropping systems, a comprehensive study of the effect of maize-legume intercrops on the diversity and abundance of entomofauna is needed to create techniques that could be used to reduce the potential for pest infestations.…”
Section: Survey Methodologysupporting
confidence: 92%
“…However, oviposition choice tests conducted in Kenya ( 111) also found that FAW laid similar number of eggs on D. intortum as on maize plants, and larvae could develop on D. intortum plants. In this region, Brachiara grasses were suggested as possible pull plants because FAW females oviposited similarly on these plants as on maize plants (111). Examples of intercropping experiments in Congo's Kashusha district also reported less frequent FAW attack on onion when intercropped with groundnut (17).…”
Section: Host Plant Usementioning
confidence: 98%
“…Results indicated that FAW could complete the life cycle on all tested host plants, but the developmental duration, pupal weight, pre-adult survival rate and APOP of FAW reared on maize were signi cantly preferable than those of FAW reared on other host plants. Several studies have also shown the high adaptability of FAW to maize (Pitre et al 1983;Scheidegger et al 2021;Liu et al 2022). Unexpectedly, the adaptability and preference of FAW to red bean and yardlong bean were also strong, not much less than that of maize, but much better than that of the other three beans, especially in terms of pre-adult survival rate.…”
Section: Occurrence Of Faw To Push-pull Cropping Of Maize and Beansmentioning
confidence: 97%
“…. A previous report byScheidegger et al (2021) showed that special volatiles released by some leguminous plants have repellent in uences upon FAW. Liu et al (2022) also found the feeding rate of FAW on faba bean was the lowest in the preference test.…”
mentioning
confidence: 93%